PEMURNIAN DAN KARAKTERISASI PEDIOSIN YANG DIPRODUKSI OLEH Pediococcus pentosaceus 2A2 - Ni Wayan Triwulandhari; Betty S. L. Jenie; Hanifah N. Lioe; Irma Isnafia Arief (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
Pediocin production by Pediococcus pentosaceus 2A2 was done in 30% molasses based medium at 37°C for 24 hours. The culture was then centrifuged to separate the cells and yield cell-free supernatant (CFS). Purification of the CFS was carried out by stepwise ammonium sulfate precipitation to achieve a 90% concentrate, followed by dialysis using membrane with a molecular weight cut off 2.0 kDa resulting in pediocin crude extract (PCE). The PCE was purified by cation exchange chromatography using SP Se-phadex C-25 and eluted with sodium acetat buffer at pH of 5.5; 6.0; 6.5; and 7.0 successively resulting in 4 fractions (F1, F2, F3, F4). Each purification step resulted in the increase in antimicrobial activity against Listeria monocytogenes ATCC 7644. The PCE had specific antimicrobial activity up to 5 fold higher than the CFS. F4 fraction, which showed the largest inhibition zone among the other fractions, had a very high specific activity up to 435 fold higher than the CFS. The SDS-PAGE analysis suggested that the molecular weight of F4 was approximately 5.9 kDa. The minimum inhibitory concentration (MIC) of F4 to inhibit 1 log (90%) of L. monocytogenes ATCC 7644 was 143 ppm. The inhibitory phenomenon observed under scanning electron microscope (SEM) showed that L. monocytogenes’s cells exposed to F4 experience morphological changes such as cells shrinkage.